2020
DOI: 10.21037/jtd-20-1328
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinoscopy-assisted transhiatal esophagectomy versus thoraco-laparoscopic esophagectomy for esophageal cancer: a single-center initial experience

Abstract: Background: We aimed to compare mediastinoscopy-assisted transhiatal esophagectomy (MATHE) with thoraco-laparoscopic esophagectomy (TLE) for patients with esophageal cancer in terms of the clinical effectiveness and perioperative complications. Methods: In total, 98 patients who underwent esophagectomy consecutively for esophageal squamous cell carcinoma in our center from Jan. 2018 to Dec. 2019 were included in this study. Thirty patients underwent mediastinoscopy-assisted and laparoscopic transhiatal esophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…About 50% of the world's EC incidence and mortality rates are noted in China (1,5). With an attempt to improve the surgical cure of EC in elderly patients, various minimally invasive and endoscopic surgical procedures for malignant esophageal tumors have been described in recent years, focusing on reducing complications and achieving rapid recovery (6)(7)(8). While some foreign studies have reported the nutritional support for recovery from surgery for EC in elderly patients (9), few Chinese articles have investigated this topic.…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of the world's EC incidence and mortality rates are noted in China (1,5). With an attempt to improve the surgical cure of EC in elderly patients, various minimally invasive and endoscopic surgical procedures for malignant esophageal tumors have been described in recent years, focusing on reducing complications and achieving rapid recovery (6)(7)(8). While some foreign studies have reported the nutritional support for recovery from surgery for EC in elderly patients (9), few Chinese articles have investigated this topic.…”
Section: Discussionmentioning
confidence: 99%
“…it is easy to damage these important adjacent structures during the operation in the narrow mediastinal space (10).…”
Section: Discussionmentioning
confidence: 99%
“…The lower thoracic esophagus was separated through the esophageal hiatus, and the lymph nodes on the side of the cardiac and lower pulmonary veins were cleared. After the above operation, a vertical incision of 5 cm was made under the xiphoid process, and the stomach was pulled out from the body to form a tubular stomach (10). The tubular stomach was pulled to the neck through the posterior mediastinum.…”
Section: Nss Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the introduction of new adjuvant treatment programs, people have gradually strict requirements for the accuracy of the diagnosis and staging of lung cancer before treatment [2] . In addition, the limitations of traditional imaging diagnostic methods such as CT and PET in the staging of lung cancer have gradually emerged, so that the application value of mediastinoscopy in the staging of mediastinal lymph nodes of lung cancer and the establishment of standardized treatment plans have gradually attracted people's attention [3] . However, due to the limitation of its own equipment, the traditional mediastinoscopy operation has shortcomings such as narrow surgical field and only one-handed operation, which further reduces the diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 99%